Risk Factors for Reoperation After Arterial Switch Operation. Issue 4 (July 2021) - Patel, Parth M.; Herrmann, Jeremy L.; Bain, Eric; Ladowski, Joseph M.; Colgate, Cameron; Rodefeld, Mark D.; Turrentine, Mark W.; Brown, John W.
Objective: The timing and nature of and risk factors for reoperation after the arterial switch operation in the setting ofd -transposition of the great arteries requires further elucidation. Methods: A total of 403 patients who underwent arterial switch operation from 1986 to 2017 were reviewed. Institutional preference was for pulmonary artery reconstruction using a pantaloon patch of fresh autologous pericardium. The targets for coronary artery reimplantation were identified by intermittent root distension. Multivariable analysis was used to identify risk factors for reoperation. Results: Median follow-up was 8.6 years (interquartile range [IQR]: 2-16.9). Pulmonary arterioplasty was the most common reoperation (n = 11, 2.7%) at 3.3 years (IQR: 1.4-11.4) postoperatively. Subvalvar right ventricular outflow tract reconstruction (RVOTR) was required in nine (2.2%) patients at 2.5 years (IQR: 1.1-5.3) postoperatively. Aortic valve repair or replacement (AVR/r) was required in seven (1.7%) patients at 13.6 years (IQR: 10.0-15.8) postoperatively. Aortic root replacement (ARR) and Coronary Artery Bypass Graft/coronary patch arterioplasty were required in five (1.2%) patients each at 13.6 years (IQR: 11.0-15.3) and 11.3 years (IQR: 2.3-13.6) postoperatively, respectively. Taussig-Bing anomaly was a risk factor for any reoperation ( P = .034). Risk factors for specific reoperations included ventricular septal defect for AVR/r ( P = .038), Taussig-Bing anomaly for RVOTR ( P = .004), and pulmonary artery banding for ARR ( P = .028). Conclusions: Pantaloon patch pulmonary artery reconstruction and intermittent neo-aortic root distension during coronary reimplantation have minimized respective outflow tract reoperations. Certain anatomic subsets carry different risks for late reoperation, and pulmonary artery and/or RVOT reinterventions tend to occur sooner than aortic reinterventions. Special attention to these higher risk subpopulations will be critical to optimizing lifelong outcomes.